FEATURES OF THE DEVELOPMENT OF HEALTH AND SOCIAL SECURITY OF SOVIET PRISONERS IN INSTITUTIONS OF CONFINEMENT IN 1956-1991 - Dmitry Yushchenko (Гуманитарные и юридические исследования)
The article studies actual problems of domestic and medical support of Soviet convicts that served sentences in correctional institutions in 1956-1991, when the system of correctional labor colonies was developed and functioning instead of the previously existing one - the main management of the camps. On the basis of the analysis of archival documents and materials of the special periodic literature, including containing results of departmental (bodies of Prosecutor's office) and other (Supervisory commissions) inspections of places of imprisonment the author reveals the features and problems taking place in connection with the penitentiary (corrective-labor) policy pursued by the Soviet state in the sphere of household and medical support of the Soviet convicts during the studied period and its influence on microsocial conditions of serving sentences. The most significant are the following problems: the protracted nature of the development of an extensive way of providing medical care to convicts of correctional labor colonies, which gives mainly quantitative rather than qualitative effect in medical care in General; the entry of medical institutions into the correctional labor colonies, which led to changes in the administrative management of the institution (instead of the doctor head of the colony) and, as a consequence, the reduction of the level of medical and household support of convicts; the need to improve the skills of doctors and nurses, as well as other personnel in the correctional institution; intentional self-harm of convicts in order to obtain more comfortable conditions of serving sentences and exemption from compulsory work. In this regard, the author summarizes the conclusion that features, as well as problems, medical and consumer services of convicts are caused by a set of factors arising both from the relationship of the administration (employees) of correctional institutions and special contingent (including those violating the regime of serving the sentence), and in connection with the policy pursued by the state, aimed at the use of virtually free labor of convicts. Socio-political and socio-economic factors also played a role in the issue under study.